The Cingulata (Mammalia, Xenarthra) collected by Santiago Roth at Alto Río Cisnes (Río Frías Formation, Miocene), Chile - Gonzalez Ruiz, Laureano Raul (2019)
The type fauna (Friasian sensu stricto) for the Friasian South American Land Mammal Age (Friasian sensu lato because includes Friasian sensu stricto, Colloncuran, Laventan and Mayoan) came from Río Frías Formation (14.83 Ma 40Ar/39Ar Ma, Langhian, Middle Miocene) at Alto Río Cisnes (Aysén, Chile) and was first collected by Santiago Roth during 1897–1898...